Severe developmental bone phenotype in ClC-7 deficient mice - Neutzsky-Wulff A. (2017)
Bone development is dependent on the functionality of three essential cell types: chondrocytes, osteoclasts and osteoblasts. If any of these cell types is dysfunctional, a developmental bone phenotype can result. The bone disease osteopetrosis is caused by osteoclast dysfunction or impaired osteoclastogenesis, leading to increased bone mass. In ClC-7 deficient mice, which display severe osteopetrosis, the osteoclast malfunction is due to abrogated acidification of the resorption lacuna. This study sought to investigate the consequences of osteoclast malfunction on bone development, bone structure and bone modeling/remodeling in ClC-7 deficient mice. Bones from wildtype, heterozygous and ClC-7 deficient mice were examined by bone histomorphometry and immunohistochemistry. ClC-7 deficient mice were found to have a severe developmental bone phenotype, characterized by dramatically increased bone mass, a high content of cartilage remnants, impaired longitudinal and radial growth, as well as lack of compact cortical bone development. Indices of bone formation were reduced in ClC-7 deficient mice; however, calcein labeling indicated that mineralization occurred on most trabecular bone surfaces. Osteoid deposition had great regional variance, but an osteopetrorickets phenotype, as observed in oc/oc mice, was not apparent in the ClC-7 deficient mice. A striking finding was the presence of very large abnormal osteoclasts, which filled the bone marrow space within the ClC-7 deficient bones. The development of these giant osteoclasts could be due to altered cell fate of the ClC-7 deficient osteoclasts, caused by increased cellular fusion and/or prolonged osteoclast survival. In summary, malfunctional ClC-7 deficient osteoclasts led to a severe developmental bone phenotype including abnormally large and non-functional osteoclasts. Bone formation paremeters were reduced; however, bone formation and mineralization were found to be heterogenous and continuing. © 2010 Elsevier Inc.